IUFRO international symposium: integrated management of neotropical rain forests by industries and communities, applying research results, involving stakeholders and defining policy - Sabogal, C.; Macedo Silva, J.N. (2001)
This paper contains brief information on the objective of the symposium and the symposium program themes: industrial forest management, community forest management and means to promote the adoption of sustainable forest management. It followed by main conclusions and recommendations.